Research progress on the natural products in the intervention of myocardial infarction - Guo, Qiuting; Wang, Jinhui; Ni, Caixia; Pan, Jiaojiao; Zou, Junbo; Shi, Yajun; Sun, Jing; Zhang, Xiaofei; Wang, Deng; Luan, Fei (Frontiers in Pharmacology, 2024)
Coronary heart disease is a prevalent cardiovascular ailment globally, with myocardial infarction (MI) being one of its most severe manifestations. The morbidity and mortality of MI are escalating, showing an increasing trend among younger, highly educated individuals, thereby posing a serious threat to public health. Currently, thrombolysis, percutaneous coronary intervention, and coronary artery bypass grafting are the primary clinical treatments for MI. Although these methods significantly reduce patient mortality, complications often result in poor prognoses. Due to limitations in chemical synthetic drug research, the focus has shifted towards developing herbs based on natural substances. Natural medicines represent a novel approach for safer and more effective MI management and treatment. They can control multiple pathogenic variables by targeting various pathways and systems. This paper investigates the molecular mechanisms of MI and evaluates the application of natural products and medicinal plants in MI treatment over the past five years, demonstrating their specific good therapeutic potential and superior tolerance. These natural therapies have been shown to mitigate myocardial cell damage caused by MI through mechanisms such as oxidative stress, inflammation, apoptosis, angiogenesis, myocardial fibrosis, autophagy, endoplasmic reticulum stress, mitophagy, and pyroptosis. This review offers the latest insights into the application of natural products and medicinal plants in MI treatment, elucidating their mechanisms of action and serving as an important reference for MI prevention.